Effect of artificial aging on the microstructure and mechanical properties of aluminum alloy AA6061-T6 - Toozandehjani, Meysam; Mustapha, Faizal; Ariffin, Mohd Khairol Anuar; Zahari, Nur Ismarrubie; Matori, Khamirul Amin; Ostovan, Farhad; Fadaeifard, Firouz (Springer, 2016)
The properties of aluminum alloy AA6061-T6 after aging at 220°C for 0.5 – 8 h are studied by the methods of light and scanning electron microscopy and fractography. The mechanical characteristics of the alloy are determined by tensile tests.